From the Valleys to the Highlands: Nahua Conquistadors in Sixteenth Century Guatemala - Ovando, Cesar (The Toro Historical Review, 2021)
The sixteenth-century Spanish conquest in the Americas has significantly altered world history. Unfortunately, the historical narrative of the conquest has predominately been narrated from a Eurocentric perspective. This situation has enabled the Spanish conquistadors to entitle themselves to an elite culture with little to no opposition. The interpretation from this narrative ultimately marginalizes the acknowledgment of indigenous participation and contribution to the Spaniards’ success. Despite the circumstances, recent scholars like Matthew Restall have pushed against the biased triumphalist narrative by turning to archival material, specifically, indigenous language texts, to uncover and amplify the Americas’ indigenous perspectives during the conquest. This trend became the New Conquest History. Generally, the scope of this study traditionally focuses on Central Mexico and Peru. However, scholarship have expanded the New Conquest History into other regions of the Americas. This includes Guatemala, which sets foot into the entire Central America region and diverse cultures.